Is there a fetal effect with low to moderate alcohol use before or during pregnancy?. Issue 4 (December 1990) - Walpole, I; Zubrick, S; Pontré, J
Abstract : STUDY OBJECTIVE–The aim was to investigate the effect of low or moderate alcohol consumption upon fetal outcome. DESIGN–This was a prospective randomised cohort study with mother and infant follow-up sample stratified on level of maternal alcohol intake. SETTING–A large maternity hospital in Western Australia. PARTICIPANTS–2002 randomly selected pregnant women were recruited over a 3 year period for questionnaire survey (19 mothers refused participation). From 665 women in a stratified subsample selected on the basis of prepregnancy alcohol consumption, 605 newborns were available for study. INVESTIGATION AND MAIN RESULTS–All 2002 women completed a comprehensive questionnaire on demographic, lifestyle (including diet), health, and obstetric factors. Of the 665 mothers who were followed through pregnancy, 605 liveborns were available at birth for measurement and detailed clinical evaluation. Low to moderate prepregnancy maternal alcohol intake was not associated with any untoward effect upon weight, length, head circumference at birth, or clinical well-being as indicated by Apgar score, respiratory distress syndrome, and overall clinical state. Other factors, particularly nicotine, were of much greater importance. CONCLUSIONS–This study fails to show any significant relationship between low to moderate prepregnancy maternal alcohol intake and newborn clinical status. The outcome suggests that cautionary advice to pregnant women warning that any alcohol taken during pregnancy is potentially harmful to the fetus is inaccurate and therefore probably counterproductive.